Answer:
The slope is 4 and y-intercept is actually 3... (I hope)
Remember rise over run, here you can see that it goes up 4 and over 1.
I am so sorry, I'm not good at explaining
We are given the function:
g(x) = 6 (4)^x
Part A.
To get the average rate of change, we use the formula:
average rate of change = [g(x2) – g(x1)] / (x2 – x1)
Section A:
average rate of change = [6 (4)^1 – 6 (4)^0] / (1 – 0) =
18
Section B:
average rate of change = [6 (4)^3 – 6 (4)^2] / (3 – 2) =
288
Part B.
288 / 18 = 16
Therefore the average rate of change of Section B is 16 times
greater than in Section A.
<span>The average rate of change is greater between x = 2 to x = 3 than between
x = 1 and x = 0 because an exponential function's rate of change increases
with increasing x (not constant).</span>
Answer:
comment the question I will try to solve it.....
Answer:

Step-by-step explanation:
To the find the equivalent of
, evaluate the expression. Start by opening the bracket.


Pair like terms


The equivalent of
is 